2016
DOI: 10.17148/iarjset.2016.3639
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Utilization of Rebar Stock for Cutting Processes in Housing Project

Abstract: Abstract:The cutting processes of rebar stock in housing project cause a large amount of waste because of high variety between required rebar lengths and standard rebar lengths, this problem is called one dimensional cutting stock problem. This research aims to utilize the rebar stock and minimize the losses using integer linear programming approach-aided by Advanced Interactive Mathematical Modeling System (AIMMS) software for solving the problems. These one-dimensional cutting rebar stock problems are divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Therefore, it is confirmed that there are not many articles directly dealing with this topic. As shown in Table 5, 37 articles were published in the journal [3,4,6,[8][9][10][11][12]63, and 11 articles were published in peer reviewed conference publication [7,55,62,71,[111][112][113][114][115][116][117]. The rest have three dissertations [5,118,119] and one book chapter [120].…”
Section: Descriptive Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it is confirmed that there are not many articles directly dealing with this topic. As shown in Table 5, 37 articles were published in the journal [3,4,6,[8][9][10][11][12]63, and 11 articles were published in peer reviewed conference publication [7,55,62,71,[111][112][113][114][115][116][117]. The rest have three dissertations [5,118,119] and one book chapter [120].…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Adjusting lap splice position to satisfy structural code to make the length of rebars used for cutting patterns constant [6,7,12,86,105,108,112,119] StL Performing CWM on rebar in stock or market length [3,4,6,[9][10][11]86,90,104,105] SpL Performing CWM on rebars with special ordered length [3,4,6,10,90] As shown in Table 10, 10 rebar CWM-related articles are described for rebars of stock length (StL) or market length. This is because the CSP study on the optimization of the material of one-dimensional stock length stored in the factory is the beginning of rebar CWM.…”
Section: Lspmentioning
confidence: 99%
See 2 more Smart Citations
“…Rebar cutting waste (RCW) is generally estimated to be 3-5% in the construction planning stage [1][2][3][4]. However, technology to reduce RCW was not developed at the construction field, so more than 5% is generated in the actual construction [5][6][7][8][9]. To solve this problem, many studies was conducted to minimize RCW [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%